2022
DOI: 10.3390/membranes12030325
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Membranes for Acute Kidney Injury

Abstract: Mortality and morbidity rates among critically ill septic patients having acute kidney injury (AKI) are very high, considering the total number of deaths after their admission. Inappropriate selection of the type of continuous renal replacement therapy and inadequate therapy become the immediate causes of these issues. Dialysis is a commonly used treatment intended to prolong the life of AKI patients. Dialysis membranes, which are the core of dialysis treatment, must be properly selected to ensure fair treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Therefore, such membranes are not in the scope of this present review. For further details about structures and features of other types of synthetic (e.g., polyacrylonitrile (PAN), polymethylmethacrylate (PMMA), polyester polymer alloy (PEPA), ethylene-vinyl alcohol co-polymer (EVAL)), cellulose-based or composite membranes, the interested reader is referred to excellent reviews in this field [ 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such membranes are not in the scope of this present review. For further details about structures and features of other types of synthetic (e.g., polyacrylonitrile (PAN), polymethylmethacrylate (PMMA), polyester polymer alloy (PEPA), ethylene-vinyl alcohol co-polymer (EVAL)), cellulose-based or composite membranes, the interested reader is referred to excellent reviews in this field [ 9 , 10 , 11 , 12 , 13 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to this classification, the small water-soluble compounds are included in the first class characterized by the molecular weight up to 500 Da (e.g., urea). Following, the second class of compounds includes medium- and large-sized molecules (MW >500 Da) such as β2-microglobulin (β2-m), complement factor D, α1-macroglobulin, and many pro-inflammatory cytokines [ 45 ]. Notably, an increasing number of studies reported that many middle-size compounds exert multi-organ toxicity by inducing systemic hyper-inflammation, resulting in tissue damage and cardiovascular diseases.…”
Section: Immunological Dysfunction In Hdmentioning
confidence: 99%
“…In the last decades, several studies reinforced the concept of considering dialysis membranes not just as a simple diffusive device but as a tool to tailor a dialysis procedure to improve the global quality of life of ESRD patients [ 45 ]. This opens a wide area of investigation, notably for the management of immunological dysfunction of ESRD patients.…”
Section: Pmma Can Ameliorate Immunological Impairment During Hdmentioning
confidence: 99%
“…Over the last six decades, hemodialysis treatment has evolved to improve the life of kidney failure patients, i.e., not just to remove uremic toxins, e.g., urea and creatinine from blood but also to keep them healthy doing daily activities. The major developments of this technology include biocompatible and high-performance dialyzers, sophisticated monitoring systems that provide online clearance, volumetric and temperature controls, and convective modalities such as hemofiltration and hemodiafiltration [1][2][3]. Yet, the core design of the hemodialysis components especially the dialyzer remains relatively unchanged ever since their invention by William J. Kolff.…”
Section: Introductionmentioning
confidence: 99%